2022
DOI: 10.3390/cancers14225635
|View full text |Cite
|
Sign up to set email alerts
|

Association between CD8+ Tumor Infiltrating Lymphocytes and the Clinical Outcome of Patients with Operable Breast Cancer Treated with Adjuvant Dose-Dense Chemotherapy—A 10 Year Follow-Up Report of a Hellenic Cooperative Oncology Group Observational Study

Abstract: Tumor-infiltrating lymphocytes (TILs) contribute to breast cancer (BC) prognosis. We investigated the prognostic impact of CD8+ TILs in patients with early breast cancer treated with adjuvant chemotherapy in a large observational clinical trial. Along with a 10 year follow-up, considering the efficacy and safety, we report the results of the translational part of our study. We examined the patients’ tumors for total (t), stromal (s), and intratumoral (i) CD8 lymphocyte density (counts/mm2) on tissue-microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
1
1
Order By: Relevance
“…investigated the linkage of TILs to clinical outcomes in BC and found that the infiltration of CD8 was correlated to a higher Ki67 index. 23 , 24 Our present analysis found no evidence to support this correlation; this contradiction might be justified by the small number of samples with Ki67 data that were available for analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…investigated the linkage of TILs to clinical outcomes in BC and found that the infiltration of CD8 was correlated to a higher Ki67 index. 23 , 24 Our present analysis found no evidence to support this correlation; this contradiction might be justified by the small number of samples with Ki67 data that were available for analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…Immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) were performed as previously described [ 30 , 31 ] on tissue microarrays (TMAs) consisting of 1.5 mm diameter tissue cores. Briefly, 3 μm of ΤΜΑ tissue sections were subjected to IHC staining with the corresponding antibodies in a Bond Max autostainer (Leica Microsystems, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…High densities of CD8+ TILs have consistently been associated with better clinical outcomes, including improved overall survival and disease-free survival. However, some studies have additionally emphasized the significance and prognostic relevance of stromal TILs [74]. Higher stromal TIL levels are linked to a better outcome in HER2+ BC patients [43].…”
Section: Investigating the Prognostic Value Of Tils In Breast Cancermentioning
confidence: 99%